Please, understand why village midwife performance is not optimum! - Indrayani, -; Harianis, Sandra; Ritasari, Mia; Astuti, Haryati; Sari, Nurul Indah; Sari, Dewi E A; Madinah, -; Dianty, Nova; Rini, Ana VP (Bangladesh Journal of Medical Science, 2017)
Background: Mother and babys death is still a global isue. The presence of village midwife has been proved effective in decreasing pains and deaths. However, in the past few years, the contribution of village midwife in preventing deaths is questioned. The low performance of village midwife is regarded as the reason why the isue exists. Objective: To find out the reasons why village midwife performance is not optimum. Design. The study used mixed methods with sequencial exploratory strategy. The study was started by collecting qualitative data, which was then followed by collecting quantitative data. The collecting of qualitative data was done by having focus group discussion (FGD) and thorough interviews, while the collecting of quantitative data was conducted by fulfilling questionaires. Setting: These activities had been carried out from August to November 2016 in 27 subdistricts in Indragiri Hilir Regency. Participants: The data collecting was done by involving 5 facilitators, 2 interviewers, and 27 data collecting officers. There were 77 midwives who had been involved in FGDs, meanwhile 31 midwives were involved in thorough interviews and 439 midwives took part in fulfilling questionaires. Results: The obstacles which make the village midwife performance not optimum include health policies and regulations, competency, tools and infrastructure, demography, geography, security and safety, midwife intrinsic and family. Conclusions: Problems faced by village midwives are too complicated to overcome by midwives alone. The government should re-examine the policies and the regulations of village midwife, the standard of tools and infrastructure, incentives, sanctions and rewards. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.505-514 =========================================================== The article with DOI: <a href="http://dx.doi.org/10.3329/bjms.v16i4.33603" target="_blank" data-saferedirecturl="https://www.google.com/url?hl=en&q=http://dx.doi.org/10.3329/bjms.v16i4.33603&source=gmail&ust=1507880518774000&usg=AFQjCNFAoKsmSHRgRVpnWkBDrGrKwz_68g"> http://dx.doi.org/10.3329/bjms.v16i4.33603 Why do teenagers get married and pregnant in early age and how is their marriage life? [Authors: Indrayani Indrayani, Juniyarti Putri Wijaya Muhammad, Dahlan H Ahmad] was published on August 2017. There was a printing mistake in the authorline and title which was absolutely unintentional. To avoid any misunderstanding, the Editorial Board of BJMS retracted it on October 2017. They replaced it with correct title and authorline. The corresponding author Indrayani is the corresponding author of both title.